Identification of biotic and abiotic factors coal mine overburden on Warukin rock formation of South Kalimantan - Fitriana, Ilma; Novianti, Vivi; H. Marrs, Rob; Widodo, Kukuh; Humami, Dhimas Wildan; Nugroho, Akhmed David (Journal of Degraded and Mining Lands Management, 2024)
Overburden (the dumping of mine tailings and other reject materials) from the Warukin geological formation is one of the potential acid-forming (PAF) of 33.17%. Mining can cause overburden to be exposed and affect biotic and abiotic conditions. The study aimed to analyze the biotic and abiotic factors of three different age overburdens from the Warukin Formation, South Kalimantan. Biotic factor measurements included vegetation sampling using line transect, soil insects using pitfall traps, and microbial using total plate count. Abiotic factor measurements included air temperature and humidity, light intensity, temperature, moisture, and pH of the substrate (n=3), and chemical overburden. Identification of plants and insect species using information from locals, identification books, and websites. Plant species diversity was analyzed using the Shannon-Wiener Index. Dominance species were analyzed using the Important Value Index (IVI). The relation of overburden age on biotic and abiotic factors was analyzed multivariate with Non-Metric Multidimensional Scaling (NMDS). The results showed that there are 102 species of plants and 11 species of soil insects. The numbers of fungi and bacteria are 10-4 CFU g-1 and 10-3 CFU g-1, respectively. Plant species diversity is classified as medium (H'= 2.34; 2.50 and 2.82). Changes in plant composition occurred as the microclimate and substrate nutrition improved. The organic matter increased over time. Humidity and light intensity influence the presence and composition of organisms, while pH values affect the adaptability of plants, insects, and microbes. Heavy metal concentrations have increased due to the physicochemical properties of the Warukin formation overburden.